2009
DOI: 10.1007/s10971-009-1907-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of silicate polymers

Abstract: In this work an inorganic polymer is developed based on Elkem microsilica and potassium hydroxide. Using experimental data and the partial charge model a model for the gelation is suggested based on the hydrolysis and condensation reactions occurring during synthesis. In addition the optimal composition of the binder system was determined using compressive strength test and solubility experiments. Based on partial charge calculations and experimental data for the hydroxide concentration and the viscosity obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…The increase in the intensity can be explained by the dissolution of microsilica leading to a greater amount of silicate species in the solution. The pH evolution during the dissolution process reported in previous work [20] indicates that the dissolution process proceeds for approximately 10 h correlating with the observed increase in silicate species. The rapid drop in the intensity observed after 12 h in Fig.…”
Section: Evolution Of Silicate Species During Polymerization Of Koh Bsupporting
confidence: 82%
See 3 more Smart Citations
“…The increase in the intensity can be explained by the dissolution of microsilica leading to a greater amount of silicate species in the solution. The pH evolution during the dissolution process reported in previous work [20] indicates that the dissolution process proceeds for approximately 10 h correlating with the observed increase in silicate species. The rapid drop in the intensity observed after 12 h in Fig.…”
Section: Evolution Of Silicate Species During Polymerization Of Koh Bsupporting
confidence: 82%
“…From the figure it is seen that the particle size of the polymer increase rapidly between 8 and 12 h suggesting polymerization. In addition previous studies of the same system have shown that the viscosity changes during synthesis [20]. It was found that the viscosity of the solution started to increase approximately 10 h after mixing also suggesting polymerization.…”
Section: Evolution Of Silicate Species During Polymerization Of Koh Bmentioning
confidence: 51%
See 2 more Smart Citations
“…In previous work, inorganic polymers have been synthesized by a sol-gel process in which the silicate precursors were formed in situ by dissolution of amorphous silica particles (microsilica, Elkem 983 U) by an alkaline solution (0.75-4 M KOH) [3]. The dissolution of the amorphous silica in alkaline conditions can be expressed by the following reactions.…”
Section: Introductionmentioning
confidence: 99%